Surgical Management and Adjuvant Therapy for Patients With Neurological Deficits From Vertebral Hemangiomas: A Meta-Analysis. Issue 2 (15th January 2020) - Piper, Keaton; Zou, Liling; Li, Dongmei; Underberg, Daniel; Towner, James; Chowdhry, Amit K.; Li, Yan Michael
Abstract : Study Design: Meta-analysis. Objective: To understand the benefits and limitations of surgical management and adjuvant therapies for patients presenting with neurological deficits from vertebral hemangiomas (VH). Summary of Background Data: VH is the most common benign spine tumor but rarely causes symptoms. Patients with back pain alone are treated with conservative management (kyphoplasty and radiation therapy), while those with neurological deficits require complex multi-modal treatment plans. Methods: A PubMed literature search for "symptomatic vertebral hemangioma with spinal cord compression" identified 47 articles. From these articles and their references, 19 observational studies on patients who underwent surgery for VH met inclusion criteria. Meta-analyses were performed comparing outcomes of the surgical and adjuvant therapies using Stata13 software. For those with insufficient data for meta-analyses, descriptive analyses of variables were completed. Results: One hundred ninety seven surgical cases of VH with neurologic deficits were identified. Surgery provided a complete remission of symptoms in 84% of patients, however 18% of patients had recurrence of hemangioma. Adjuvant interventions included radiation, embolization, and kyphoplasty. Radiation therapy (XRT) was associated with a lower recurrence rate and an increase in minor transient adverse effects. Preoperative embolization performed in 98 patients was associated with improved symptoms, reduced complications, lower recurrence rate, less blood loss, and higher incidence of pathologic vertebral fractures. Meta-analyses did not yield statistically significant results, likely due to the heterogeneity amongst the studies and small sample sizes, but the results compiled together provide insight on potential benefits of preoperative embolization for symptomatic relief and reduced risk of recurrence with XRT that deserves further study. Conclusion: For patients with neurologic deficits from spinal cord or nerve root compression, surgery provides improvement in symptoms. Recurrence of VH and symptoms refractory to surgery can be further reduced by adjuvant therapies such as embolization, kyphoplasty, and radiation with some unique risks to each therapy. Level of Evidence: 2 Abstract : This analysis is a succinct summary of the literature on adjuvant therapies and surgical approaches for vertebral hemangiomas producing neurologic deficits. Meta-analyses on adjuvant embolization, radiation therapy, and kyphoplasty were conducted. Embolization and radiation therapy have unique potential benefits when analyzing studies individually but were not significant by meta-analyses.